Observation of New Resonances in the Λ0bπ+π− System - Aaij R. Roel; Beteta C. A. Carlos Abellan; Ackernley T.; Eydelman S. I. Semen Isaakovich; Kharisova A. E. Anastasiya Evgenjevna; Panshin G. L. Gennady Leonidovich; Strokov S. A. Sergey Aleksandrovich (2019, 2019)
Title screen